1987
DOI: 10.1093/petrology/28.1.75
|View full text |Cite
|
Sign up to set email alerts
|

REE Variations Across the Peninsular Ranges Batholith: Implications for Batholithic Petrogenesis and Crustal Growth in Magmatic Arcs

Abstract: Rare earth element (REE) patterns of plutonic rocks across the Cretaceous Peninsular Ranges batholith vary systematically west to east, transverse to its long axis and structural trends and generally parallel to asymmetries in petrologic, geochronologic and isotopic properties. The batholith can be divided into three distinct parallel longitudinal regions, each defined by distinct REE pattern types. An abrupt transition occurs between rocks with slightly fractionated REE patterns in the western (coastal) regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
184
0
4

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(199 citation statements)
references
References 57 publications
11
184
0
4
Order By: Relevance
“…The PRB represents part of the north-south trending Cordilleran batholiths emplaced through the western margin of North America during Cretaceous subduction of the Farallon plate. The eastern PRB represents the part of the continental arc that was emplaced through the Paleozoic margin of North America and hence represents mixtures of juvenile magmas and melts of older metamorphic basement (27) (4,20,26). Despite the involvement of older, metamorphic basement, all of the granitic rocks studied here belong to the I-type granitic series (11).…”
Section: Application To Continental Arc Granitoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRB represents part of the north-south trending Cordilleran batholiths emplaced through the western margin of North America during Cretaceous subduction of the Farallon plate. The eastern PRB represents the part of the continental arc that was emplaced through the Paleozoic margin of North America and hence represents mixtures of juvenile magmas and melts of older metamorphic basement (27) (4,20,26). Despite the involvement of older, metamorphic basement, all of the granitic rocks studied here belong to the I-type granitic series (11).…”
Section: Application To Continental Arc Granitoidsmentioning
confidence: 99%
“…We selected 11 representative samples in this region. The geology of the PRB has been described in detail (20)(21)(22)(23)(24)(25)(26). The PRB represents part of the north-south trending Cordilleran batholiths emplaced through the western margin of North America during Cretaceous subduction of the Farallon plate.…”
Section: Application To Continental Arc Granitoidsmentioning
confidence: 99%
“…The rare earth element (REE) concentrations of the two suites are different as originally noted by Gromet and Silver (1987), who suggested that rocks of the Santa Ana arc were derived from partial melting of plagioclase-rich sources whereas La Posta rocks were derived from garnet-bearing assemblages. They also pointed out that generation of La Posta rocks involved a higher ÎŽ 18 O source.…”
mentioning
confidence: 79%
“…10a-b), suggesting that their source contained residual amphibole in addition to garnet (Gromet and Silver, 1987). Therefore, the Tunchang adakitic granodiorites were most plausibly produced by partial melting of basaltic lower crust in the garnet stability field whereas the Niubiling and Gaotongling adakitic granites were likely derived by partial melting of basaltic lower crust in the stability field of garnet + amphibole.…”
Section: Nd-sr-pb-hf Isotope Compositionsmentioning
confidence: 99%